Post‐buckling strength of plate girders subjected to shear – experimental verification. Issue 1 (5th October 2017) - Hansen, Thomas
Abstract: This paper describes a calculation method for steel plate girders with transverse web stiffeners subjected to shear. It may be used to predict the failure load or, as a design method, to determine the optimal number of internal web stiffeners. The method is based on the theory of plasticity. Many other theories have been developed, but the method presented here differs from these theories by incorporating the strength of the transverse stiffeners and by assuming that the tensile bands may pass the transverse stiffeners – an effect often observed in tests. Other methods have only dealt with a single web field between two stiffeners. The load‐carrying capacity may be predicted by applying both the lower‐bound and upper‐bound theorems. The upper‐bound solutions show very good correlation with existing tests. The emphasis is placed on the presentation of the tests conducted at the Technical University of Denmark. The test programme comprised six full‐scale plate girder specimens. Agreement between the theory and the tests is very good.